Penataran Solusi Meningkatkan Kinerja dan Efektivitas Kerja Karyawan UMKM Kuliner Kota Tasikmalaya - Sudirman, Rendy; Nugraha, Ferryan; Kurniawan, Heru; Kurnia, M. Ikhsan; Enas, Ujang (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2026)
The culinary segment is one of Tasikmalaya city's strengths in attracting both local and out-of-town tourists. Amidst the proliferation of culinary franchises, the food industry is striving to maintain its competitiveness with culinary companies from outside the city, which are backed by capital, brand image, and, of course, employees with superior skills compared to MSME employees who have not received training. The subject of this activity is culinary entrepreneurs in Tasikmalaya city, and the training was held at the Baso Mang Ja'i Tasikmalaya Hall. The main objective of this activity is to help provide business understanding for culinary entrepreneurs in the field of human resource management. From the results of the training, participants responded with questions related to ways to improve work effectiveness and performance, which were complained about by culinary entrepreneurs in Tasikmalaya city. Thus, it can be seen that the audience felt the direct benefits of the community service activities that had been carried out because they contained solutions to the problems faced by the attendees in these activities.